2016
DOI: 10.1182/blood-2015-12-684696
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective autophagy maintains leukemia-initiating cells in murine myeloid leukemia

Abstract: Key Points• Autophagy is required for maintenance of AML-initiating cells and peripheral myeloblast survival.• Loss of autophagy potentiates the therapeutic effects of AraC in vivo.Despite advances in the treatment of acute myeloid leukemia (AML), relapse and drug resistance frequently occur. Therefore, detailed mechanisms of refractoriness, including leukemia-initiating cell (LIC) biology, should be elucidated to treat AML. The selfdegradative property of cytosolic macromolecules is central to autophagy and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
59
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 52 publications
(56 reference statements)
9
59
0
Order By: Relevance
“…Figure 1J,K). These data are consistent with recent publications 7,8,12 , and demonstrate that Atg7 is required for the efficient generation of AML in vivo, however we note that AML penetrance was 100% even in the complete absence of autophagic flux, suggesting that full leukemic transformation may be sufficient to overcome this requirement for autophagy. Moreover, although LysM expression is active in GMPs in normal hematopoiesis, LysMCre does not efficiently excise Atg7 within LSC populations and should not be used to test gene function in AML LSC models.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…Figure 1J,K). These data are consistent with recent publications 7,8,12 , and demonstrate that Atg7 is required for the efficient generation of AML in vivo, however we note that AML penetrance was 100% even in the complete absence of autophagic flux, suggesting that full leukemic transformation may be sufficient to overcome this requirement for autophagy. Moreover, although LysM expression is active in GMPs in normal hematopoiesis, LysMCre does not efficiently excise Atg7 within LSC populations and should not be used to test gene function in AML LSC models.…”
supporting
confidence: 93%
“…Within the hematopoietic system, autophagy has diverse roles and is required for hematopoietic stem cell (HSC) function 2 , differentiation into erythroid 3 or T-lymphoid lineages 4,5 and response to extracellular cytokine signaling 6 . In blood cancers such as acute myeloid leukaemia (AML), modulating autophagy has been proposed as a novel therapy to treat AML 1,7,8 . Leukemia stem cell (LSC) populations initiate and maintain leukemia in vivo.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12 Mounts of studies indicated that autophagy played a cytoprotective role in pathogenesis process and antitumor therapy. 13 Notably, more and more evidences indicated that reactive oxygen species (ROS) were also strongly involved in the response to cancer therapeutics. 14 Thus, stimulation of autophagy by rhArg through depleting arginine and mitochondrial-derived ROS production have been highlighted in the treatment with rhArg for NSCLC.…”
mentioning
confidence: 99%
“…Moreover, mTORC-S6K1 pathway has been shown to be a critical regulator of integral cellular processes like metabolism and autophagy. Recent findings show that metabolism (72, 73) and autophagy (74-76) are critical regulators of LSC maintenance. Additionally, mTORC1-S6K1 pathway could also reprogram metabolic pathways in malignant cells to help the cells escape glycolysis dependency and become resistance to inhibition of cellular glycolysis (77).…”
Section: Future Directionsmentioning
confidence: 99%